Pairing MCL‐1 inhibition with venetoclax improves therapeutic efficiency of BH3‐mimetics in AML. (4th August 2020) - Hormi, Myriam; Birsen, Rudy; Belhadj, Maya; Huynh, Tony; Cantero Aguilar, Lilia; Grignano, Eric; Haddaoui, Lamya; Guillonneau, Francois; Mayeux, Patrick; Hunault, Mathilde; Tamburini, Jérôme; Kosmider, Olivier; et al.
Abstract: Objectives: Venetoclax combined with hypomethylating agents is a new therapeutic strategy frequently used for treating AML patients who are not eligible for conventional chemotherapy. However, high response rates are heterogeneous due to different mechanisms mediating resistance to venetoclax such as up‐regulation of MCL‐1 expression. We thus tested the anti‐leukemic activity of S63845, a specific MCL‐1 inhibitor. Methods: Apoptosis induces by S63845 with or without venetoclax was evaluated in primary AML samples and in AML cell lines co‐cultured or not with bone marrow (BM) mesenchymal stromal cells. Sensitivity of leukemic cells to S63845 was correlated to the expression level of BCL‐2, MCL‐1, and BCL‐XL determined by Western Blot and mass spectrometry‐based proteomics. Results: We observed that even if MCL‐1 expression is weak compared to BCL‐2, S63845 induces apoptosis of AML cells and strongly synergizes with venetoclax. Furthermore, AML cells resistant to venetoclax are highly sensitive to S63845. Interestingly, the synergistic effect of S63845 toward venetoclax‐mediated apoptosis of AML cells is still observed in a context of interaction with the BM microenvironment that intrinsically mediates resistance to BCL2 inhibition. Conclusion: These results are therefore of great relevance for clinicians as they provide the rational for combining BCL‐2 and MCL‐1 inhibition in AML.